ISWI and CHD Chromatin Remodelers Bind Promoters but Act in Gene Bodies - Zentner, Gabriel E. (Public Library of Science, 2013)
ATP-dependent nucleosome remodelers influence genetic processes by altering nucleosome occupancy, positioning, and composition. In vitro, Saccharomyces cerevisiae ISWI and CHD remodelers require ∼30–85 bp of extranucleosomal DNA to reposition nucleosomes, but linker DNA in S. cerevisiae averages <20 bp. To address this discrepancy between in vitro and in vivo observations, we have mapped the genomic distributions of the yeast Isw1, Isw2, and Chd1 remodelers at base-pair resolution on native chromatin. Although these remodelers act in gene bodies, we find that they are also highly enriched at nucleosome-depleted regions (NDRs), where they bind to extended regions of DNA adjacent to particular transcription factors. Surprisingly, catalytically inactive remodelers show similar binding patterns. We find that remodeler occupancy at NDRs and gene bodies is associated with nucleosome turnover and transcriptional elongation rate, suggesting that remodelers act on regions of transient nucleosome unwrapping or depletion within gene bodies subsequent to transcriptional elongation.